2023
DOI: 10.15379/ijmst.v10i2.3191
|View full text |Cite
|
Sign up to set email alerts
|

Legal Research Method: Theoretical and Implementative Review

Achmad Irwan Hamzani,
Tiyas Vika Widyastuti,
Nur Khasanah
et al.

Abstract: Legal research has methods like research in general. The process of legal research is adjusted to the legal events that occur. Legal research can be seen from various aspects. The purpose of writing this article is to describe the types, approaches, research data, data collection techniques, and data analysis methods in legal research. This research uses a conceptual approach which is still within the scope of the normative approach because it only examines the opinions that develop in the research method. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
3
0
1
Order By: Relevance
“…This investigation exclusively utilizes "secondary data" in the form of documents, particularly legal periodicals, classifying it as a form of library research. The methodology employed in this study is a conceptual approach that remains consistent with the "normative approach" [6]. The conceptual approach is grounded in expert opinion and doctrinal perspectives.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This investigation exclusively utilizes "secondary data" in the form of documents, particularly legal periodicals, classifying it as a form of library research. The methodology employed in this study is a conceptual approach that remains consistent with the "normative approach" [6]. The conceptual approach is grounded in expert opinion and doctrinal perspectives.…”
Section: Methodsmentioning
confidence: 99%
“…The term "secondary data" refers to information that has been supplied by third parties, typically in the form of documents, and was not acquired directly. This research uses "secondary data" because it only consists of written documents [6]. The data collection technique is carried out through online searches by collecting and mapping articles published in legal journals.…”
Section: Methodsmentioning
confidence: 99%
“…Data sources come from libraries that relate to the research object, whether it be books, books, journals, statute approaches related to this research. Library research with quotations of offline and internet sources (Hamzani et al, 2023). Books serve as offline sources obtaining from the study of libraries, and online sources, such as newspapers or articles related to research, are found on the Internet (Assyakurrohim, 2023).…”
Section: Methodsmentioning
confidence: 99%
“…Penelitian hukum normatif empiris ialah jenis kajian yang dipakai pada kajian ini. Penelitian hukum normatif menurutnya adalah penelitian hukum yang dilakukan melalui analisis data sekunder atau sumber kepustakaan (Hamzani et al, 2023). Sedangkan penelitian hukum empiris adalah kajian hukum yang melihat bagaimana hukum sebenarnya diterapkan dan bagaimana fungsinya dalam ruang publik.…”
Section: Metodeunclassified